The Effect of Work Discipline and Work Ethic on Employee Productivity at PT Rodaniaga Kokoh Nusantara, Tangerang Regency - Dyah Ayu Amanda; Carolus Baromeus Supartomo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study evaluates the predictive paths of work discipline and work ethic regarding employee productivity within the activated carbon manufacturing sector. Utilizing an empirical quantitative descriptive method with an associative causal framework, this investigation executes a complete census of all sixty operational personnel through a saturated sampling technique. Primary data gathered over a multi month operational horizon via closed questionnaires were processed using classical assumption diagnostics and multi variate linear regression models. The resulting econometric estimations demonstrate that work discipline exerts a positive, statistically significant partial impact on labor output limits, whereas work ethic provides a mathematically superior contribution toward optimizing total production limits. Simultaneous statistical testing confirms that the joint integration of behavioral regulations and personal reliability yields an optimal structural baseline that explains a substantial portion of floor productivity variance, while the remaining percentage depends on external variables beyond the current empirical model. Consequently, industrial human resource executives must design integrated monitoring strategies that address punctual attendance patterns while fostering collaborative workspace initiatives to ensure sustainable organizational performance.